Fib Model Code 2020: Towards a general code for both new and existing concrete structures. (3rd June 2018) - Matthews, Stuart; Bigaj‐van Vliet, Agnieszka; Walraven, Joost; Mancini, Giuseppe; Dieteren, Gerrie
Abstract : Discussions have been underway in fib (Fédération Internationale du Béton) about advancing the fib Model Code for concrete structures. These include the fib international workshop in The Hague (June 2015), the fib MC2020 Core Group meeting in Madrid (December 2015), and a series of follow‐up worldwide consultations on the fib ambition regarding the new developments in structural codes, including the special session on Model Code in the fib Symposium in Maastricht (June 2017). This paper discusses the main aspects of the development of fib MC2020, which is envisaged as a single‐merged general code fully integrating the provisions for the design of new concrete structures with matters relating to existing concrete structure. It needs to deal effectively with both the design of structures and all the activities associated with the through‐life management of existing concrete structures, including matters such as their in‐service assessment and interventions upon them. To that end, MC2020 will take sustainability as a fundamental requirement, based upon a holistic treatment of societal needs and impacts, life‐cycle cost and environmental impacts. This paper discusses the main aspects of the development of fib MC2020. As part of this, the envisaged contribution of fib T10.1: Model Code 2020 is reviewed. However, recognizing the overall ambition of the fib MC2020 project, it is clear that all fib commissions, along with other bodies able to make contributions on relevant topics, will need to work together to assemble the breadth of knowledge and expertise which will be required for the fib MC2020 project.